1998
DOI: 10.1901/jaba.1998.31-683
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Recycling in Academic Buildings: A Systematic Replication

Abstract: We placed recycling receptacles in two locations in academic buildings and studied recycling behavior within an ABA multiple baseline design. During baseline, recycling receptacles were placed in a central location. During the intervention, receptacles were moved into classrooms where beverages were primarily consumed. Baseline conditions were then reinstated. The percentage of cans recycled daily increased during intervention and returned to near-baseline levels during withdrawal. The percentage of cans disca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 3 publications
4
76
0
4
Order By: Relevance
“…Although the results of this study partially replicate previous findings that recycling bin proximity influences rates of recycling (e.g., Ludwig et al, 1998), they differ from those reported by O'Connor et al (2010) in that simply placing bins in the classrooms did not lead to a large increase in recycling. The finding that prompting in the form of informational signs improved rates of recycling was consistent with the effects reported by previous research as well (e.g., Reid, Luyben, Rawers, & Bailey, 1976).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Although the results of this study partially replicate previous findings that recycling bin proximity influences rates of recycling (e.g., Ludwig et al, 1998), they differ from those reported by O'Connor et al (2010) in that simply placing bins in the classrooms did not lead to a large increase in recycling. The finding that prompting in the form of informational signs improved rates of recycling was consistent with the effects reported by previous research as well (e.g., Reid, Luyben, Rawers, & Bailey, 1976).…”
Section: Resultssupporting
confidence: 62%
“…Researchers have successfully increased recycling through consequence-based interventions such as contingent rewards (e.g., Geller, Chaffee, & Ingram, 1975), public feedback (e.g., Kim, Oah, & Dickinson, 2005), and commitment (e.g., 1 Email: ndmiller@memphis.ed DeLeon & Fuqua, 1995). Two antecedent-based procedures that are particularly promising for institutional efforts to improve recycling are the placement of recycling bins in close proximity to the point of consumption (e.g., Ludwig, Gray, & Rowell, 1998;O'Connor, Lerman, Fritz, & Hodde, 2010), and providing antecedent prompts or signs (e.g., Austin, Hatfield, Grindle, & Bailey, 1993;Duffy & Verges, 2008). These procedures may be relatively easy and inexpensive to implement on a large scale, and require fewer resources than consequence-based strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have included a study of an intervention are: an intervention of recycling behaviour (Ludwig, Gray, & Rowell, 1998), a feedback intervention (Carrico & Riemer, 2011) and an intervention with office paper recycling (Brothers, Krantz, & McClannahan, 1994 McClannahan's (1994) intervention increased paper recycling to 85%. Gregory- Smith et al (in press) found that self-reported behaviour was lower after an intervention and suggested that this may be because, after the intervention, the employees became more critical of their behaviour.…”
Section: Campaign Awarenessmentioning
confidence: 99%
“…Foxall (1993) notes the focus of applied behaviour analysis on the effectiveness of prompts (which he states act as antecedent verbal stimuli) and highlights feedback and incentives as two types of reinforcement. These two types have largely centred on issues of social importance, such as domestic energy use (Kohlenberg, Phillips, & Proctor, 1976;Winett, Leckliter, Chinn, Stahl, & Love, 1985;Winett, Neale, & Grier, 1979), waste disposal and recycling (Brothers, Krantz, 20 & McClannahan, 1994;Craig & Leland, 1983;Ludwig, Gray & Rowell, 1998), and disease prevention (Winett, Moore, & Anderson, 1991). Because of this, interest in applied behaviour analysis from the social marketing perspective has increased (Donovan, 2011), as reflected in relevant developments in the area, such as choice architecture (Thaler & Sunstein, 2009).…”
Section: Applied Behaviour Analysismentioning
confidence: 99%